THE INFLUENCE OF PROMOTION EXPENSES, SAVINGS, AND FINANCIAL RATIOS TO DIBURSED LOANS ON BANK PEMBANGUNAN DAERAH IN INDONESIA - Sartika Sartika; Misdiyono Misdiyono (Jurnal Ilmiah Ekonomi Bisnis, 2019)
Bank as financial intermediaries have a vital function, which is collecting and distributing funds. This research is focused on disbursed loans, because it is an activity that generates the greatest income for a bank and can help public who need funds. This research is aimed to examine the influence of promotion expenses, savings, while Capital Adequacy Ratio (CAR), Gross Non Performing Loan (Gross NPL), and Return on Asset (ROA) as proxy of financial ratios in this research to disbursed loans. The objects of this research are Bank Pembangunan Daerah (BPDs) listed in Bank Indonesia (BI) and published their annual reports and financial statements which have been audited by the Public Accountants' Office in the period 2008-2012 as samples. The sampling technique uses purposive sampling with specific criteria, so that 12 BPDs are selected. The analytical method uses multiple regression analysis with SPSS version 20. The results of this research show that promotion expenses have influence on disbursed loans partially on the BPDs, savings have influence on disbursed loans, CAR has influence on disbursed loans, Gross NPL has no influence on disbursed loans, and ROA has no influence on disbursed loans. Independent variables (promotion expenses, savings, CAR, Gross NPL, and ROA) have influences on disbursed loans simultaneously on the BPDs.